High-frequency oscillations in epilepsy and surgical outcome. A meta-analysis - Höller, Yvonne; Kutil, Raoul; Klaffenböck, Lukas; Thomschewski, Aljoscha; Höller, Peter M.; Bathke, Arne C.; Jacobs, Julia; Taylor, Alexandra C.; Nardone, Raffaele; Trinka, Eugen (Frontiers in Human Neuroscience, 2015)
High frequency oscillations (HFOs) are estimated as a potential marker for epileptogenicity. Current research strives for valid evidence that these HFOs could aid the delineation of the to-be resected area in patients with refractory epilepsy and improve surgical outcomes. In the present meta-analysis, we evaluated the relation between resection of regions from which HFOs can be detected and outcome after epilepsy surgery. We conducted a systematic review of all studies that related the resection of HFO-generating areas to postsurgical outcome. We related the outcome (seizure freedom) to resection ratio, that is, the ratio between the number of channels on which HFOs were detected and, among these, the number of channels that were inside the resected area. We compared the resection ratio between seizure free and not seizure free patients. In total, 11 studies were included. In 10 studies, ripples (80-200 Hz) were analyzed, and in 7 studies, fast ripples (>200 Hz) were studied. We found comparable differences (dif) and largely overlapping confidence intervals (CI) in resection ratios between outcome groups for ripples (dif=0.18; CI: 0.10-0.27) and fast ripples (dif=0.17; CI: 0.01-0.33). Subgroup analysis showed that automated detection (dif=0.22; CI: 0.03-0.41) was comparable to visual detection (dif=0.17; CI: 0.08-0.27). Considering frequency of HFOs (dif=0.24; CI: 0.09-0.38) was related more strongly to outcome than considering each electrode that was showing HFOs (dif=0.15; CI=0.03-0.27). The effect sizes found in the meta-analysis are small but significant. Automated detection and application of a detection threshold in order to detect channels with a frequent occurrence of HFOs is important to yield a marker that could be useful in presurgical evaluation. In order to compare studies with different methodological approaches, detailed and standardized reporting is warranted.